Risk Identification and Mitigation in the Halal Black Tea Orthodox Supply Chain Using SCOR and House of Risk - Shalihin, Ahmad; Sihombing, Clarisa D; Sinulingga, Sukaria (Jurnal Sistem Teknik Industri, 2025)
The plantation sector such as tea has a complex supply chain. The production process that takes place at PTPN IV Tobasari Tea Unit is not free from various problems. Delays in the raw material processing process often occur due to raw materials not arriving according to schedule. Delays are supported by disruptions to processing machines that can hinder or even stop the production process. Therefore, it is necessary to design mitigation actions to minimize and prevent risks that occur. This study aims to identify risk-causing factors using the Supply Chain Operation Reference (SCOR) and formulate effective risk mitigation policies based on priority risk agents using the House of Risk (HOR) approach. The results of risk identification at House of Risk showed that there were 21 risk events with 4 priority risk agents where the cumulative frequency value of Aggregate Risk Potential (ARP) was 76.82%. Effective and easy mitigation actions based on the Effectiveness to Difficulty value are to conduct analysis and evaluation of employee performance. These findings provide practical implications for improving supply chain resilience in the tea industry, particularly in addressing delays and machine failures through targeted risk mitigation strategies.